2022
DOI: 10.1038/s41598-022-25699-w
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy in gastrointestinal diseases: a comparative analysis between patients with liver cirrhosis, inflammatory bowel disease and gastrointestinal cancer

Abstract: Currently, there are only few data on health literacy in patients with chronic gastrointestinal diseases such as gastrointestinal cancer, inflammatory bowel disease (IBD) and, in particular, liver cirrhosis available. Moreover, head-to-head comparisons between patients with these different diseases are lacking. In this study, 379 patients were enrolled. Of these, 102 patients had gastrointestinal cancer, 86 had IBD, and 191 had cirrhosis. Health literacy was quantified using the Health Literacy Questionnaire (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In one study, when compared to patients with gastrointestinal malignancies and inflammatory bowel disease, patients with cirrhosis were found to have the poorest understanding of their illness. 17 In this study of 379 patients, those with advanced liver disease were found to have poorer illness understanding than those who were more compensated. Another study conducted in 150 outpatients with cirrhosis highlighted deficits in disease self-management.…”
Section: Introductionmentioning
confidence: 72%
“…In one study, when compared to patients with gastrointestinal malignancies and inflammatory bowel disease, patients with cirrhosis were found to have the poorest understanding of their illness. 17 In this study of 379 patients, those with advanced liver disease were found to have poorer illness understanding than those who were more compensated. Another study conducted in 150 outpatients with cirrhosis highlighted deficits in disease self-management.…”
Section: Introductionmentioning
confidence: 72%
“…It is important to educate the young patients with IBD during family planning counseling. [ 194 200 ] Low health literacy is present in IBD populations and more common among older AAs [ 201 203 ] Opportunities exist for providing more health literacy-sensitive care in IBD to address disparities and to benefit those with low health literacy. [ 203 ] Unfortunately, to date, racial disparities and racism severely impacts AAW during pregnancies in health and diseases while attending care coordination services.…”
Section: Pregnancy and Inflammatory Bowel Disease Care Coordination T...mentioning
confidence: 99%
“…[ 194 200 ] Low health literacy is present in IBD populations and more common among older AAs [ 201 203 ] Opportunities exist for providing more health literacy-sensitive care in IBD to address disparities and to benefit those with low health literacy. [ 203 ] Unfortunately, to date, racial disparities and racism severely impacts AAW during pregnancies in health and diseases while attending care coordination services. [ 125 , 204 , 205 ] Fulminant colitis disease during conception and pregnancy in women with IBD increases the risk of pregnancy complications and adverse neonatal outcomes .…”
Section: Pregnancy and Inflammatory Bowel Disease Care Coordination T...mentioning
confidence: 99%
“…Unfortunately, patients and families often lack a thorough understanding of their illness trajectory and infrequently participate in conversations related to advance care planning (ACP). [6,7] Communication around treatment decisions are often delayed and tend to take place in the inpatient setting, where mortality is high, especially in conditions such as decompensated cirrhosis. [8][9][10][11] One reason for such delayed and limited communication in this high-risk population may be gaps in training for general and subspecialty gastroenterology (GI) fellows.…”
Section: Introductionmentioning
confidence: 99%